2015
DOI: 10.1097/iae.0000000000000836
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Effect of Anti-Vascular Endothelial Growth Factor Therapy on Treatment-Naive Choroidal Neovascularization Using Optical Coherence Tomography Angiography

Abstract: Both CNV greatest linear dimension and area measured using OCTA decreased after anti-VEGF treatment in most patients. Optical coherence tomography angiography may be a useful tool for monitoring and quantifying the response of CNV to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 22 publications
4
79
0
3
Order By: Relevance
“…Researchers also demonstrated the usefulness of OCTA in evaluating the response to anti-VEGF treatment [98,99] . OCTA has been demonstrated to be useful to identify the retinal vascular pathology in diseases such as macular telangiectasia Type 2 [100] , sickle cell retinopathy [101] , central serous chorioretinopathy (CSCR) [102] , and glaucoma [103] .…”
Section: For Retinal Vein Occlusions(rvo) Kashani Et Al Reported Finmentioning
confidence: 99%
“…Researchers also demonstrated the usefulness of OCTA in evaluating the response to anti-VEGF treatment [98,99] . OCTA has been demonstrated to be useful to identify the retinal vascular pathology in diseases such as macular telangiectasia Type 2 [100] , sickle cell retinopathy [101] , central serous chorioretinopathy (CSCR) [102] , and glaucoma [103] .…”
Section: For Retinal Vein Occlusions(rvo) Kashani Et Al Reported Finmentioning
confidence: 99%
“…26 OCTA can be used to monitor CNV after anti-vascular endothelial growth factor (anti-VEGF) treatment with reduced CNV density and size, vascular rarefication, and loss of smaller or peripheral capillaries after therapy. [27][28][29][30][31] Flow within a vascular network may be apparent on OCTA in a disciform scar from AMD. 32 One study demonstrated alterations in the retinal vasculature in early to intermediate AMD with reduced vessel density in both the superficial and deep inner retinal plexuses and reduced choroidal thickness compared with control.…”
Section: Age-related Macular Degeneration and Choroidal Neovascularizmentioning
confidence: 99%
“…Az AMD és az AMD-re adott kezelés hatására a CNV szerkezetében történő rövid távú válto-zások nemrégiben kerültek rendszerszerű leírásra [12].…”
Section: Eredeti Közleményunclassified
“…Muakkassa és Lumbroso tanulmányai a különböző tí-pusú CNV méretváltozásait követik nyomon [12,22]. Muakkassa azt tapasztalta, hogy a CNV legnagyobb lineáris kiterjedése (greatest linear dimension -GLD) 23,6%-os, míg a CNV összterülete 29,8%-os csökkenést mutatott 3 hónapos VEGF-gátló kezelés kapcsán.…”
Section: Eredeti Közleményunclassified